Kinetics of intramembrane charge movement and conductance activation of batrachotoxin-modified sodium channels in frog node of Ranvier (The Rockefeller University Press, 1985)
Sodium current and intramembrane gating charge movement (Q) were monitored in voltage-clamped frog node of Ranvier after modification of all sodium channels by batrachotoxin (BTX). Sodium current activation followed a single-exponential time course, provided a delay was interposed between the onset of the step ON depolarization and that of the current change. The delay decreased with increased ON depolarization and, for a constant ON depolarization, increased with prehyperpolarization. ON charge movement followed a single-exponential time course with time constants tau Q,ON slightly larger than tau Na, ON. For pulses between -70 and -50 mV, tau Q,ON/tau Na,ON = 1.14 +/- 0.08. The OFF charge movement and OFF sodium current tails after a depolarizing pulse followed single-exponential time courses, with tau Q, OFF larger than tau Na, OFF. tau Q,OFF/tau Na,OFF increased with OFF voltage from 1 near -100 mV to 2 near -160 mV. At a set OFF potential (- 120 mV), both tau Q,OFF and tau Na,OFF increased with ON pulse duration. The delay in INa activation and the effect of ON pulse duration on tau Q,OFF and tau Na,OFF are inconsistent with a simple two- state, single-transition model for the gating of batrachotoxin-modified sodium channels.